OPTIMALISASI PEMBELAJARAN MEMBACA AL-QUR’AN MELALUI METODE IQRO’ DI TADIKA AL-FIKH ORCHARD TAMAN SETIA - Ahmad Billah; Hasrian Rudi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to optimize learning to read the Qur'an through the Iqro' method at Tadika Al-Fikh Orchard Taman Setia Malaysia with 5 students as research subjects. By using a qualitative approach and descriptive methods, this study involves a number of techniques to collect data, namely observation, interviews, and documentation to understand the effectiveness of the Iqro' method in improving children's reading skills. The problems raised are the many children who have difficulty in reading the Qur'an in a good and correct way, as well as the lack of understanding of the right method to teach children to read the Qur'an. The results of this study are expected to provide recommendations for improving the effectiveness of learning to read the Qur'an at Tadika Al-Fikh Orchard, so that it can help children master the skills of reading the Qur'an better.